2012
DOI: 10.2174/1874943701205010001
|View full text |Cite
|
Sign up to set email alerts
|

EMG Activation of the Vastus Medialis Oblique and Vastus Lateralis During Four Rehabilitative Exercises

Abstract: Abstract:The purpose of this study was to compare four common rehabilitation exercises used in physical therapy clinics for activating the vastus medialis oblique (VMO) and vastus lateralis (VL). Thirty-four subjects, aged 22-28 years, without patellofemoral pain syndrome (PFPS) (18 females and 16 males) were recruited. Subjects performed four exercises-straight leg raise with neutral and externally rotated hip positions (SLRN, SLRER), and short arc quad with neutral and externally rotated hip positions (SAQN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…According the results of this study and previous studies, there is no agreement on muscles weakness or decrease in VMO/VL ratio [36]. Some studies reported muscles weakness and decrease in VMO/VL ratio [17,18], while others reported no significant associations in this regard [1,2,19,34]. Additionally, the effectiveness of exercises for the efficient activity of VMO muscle and improvement of VMO/VL ratio still remains unclear.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…According the results of this study and previous studies, there is no agreement on muscles weakness or decrease in VMO/VL ratio [36]. Some studies reported muscles weakness and decrease in VMO/VL ratio [17,18], while others reported no significant associations in this regard [1,2,19,34]. Additionally, the effectiveness of exercises for the efficient activity of VMO muscle and improvement of VMO/VL ratio still remains unclear.…”
Section: Discussioncontrasting
confidence: 74%
“…However, they investigated quadriceps muscle activity as a whole and disregarded different parts of quadriceps separately, and lacked a control group. Moreover, Soderberg et al reported higher activation of Rectus Femoris (RF) than vasti muscles during SLR [1,32]. Sykes and Wong reported that additional hip rotation, especially external rotation to SLR had a significant effect on the EMG amplitude of VMO [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, during walking greater EMG amplitude is observed in the medial than the lateral gastrocnemius in %50% of participants, whereas the other half has similar EMG amplitude of both muscles [9]. Similarly, during a wide range of tasks, some [10,11], but not all [12], studies report greater EMG amplitude of the lateral (vastus lateralis, VL) than the medial (vastus medialis, VM) head of the quadriceps with a large difference between individuals (e.g. ratio of VL/VM activation ranges from %0.8 to 3 [10]).…”
Section: Introductionmentioning
confidence: 96%
“…Kushion et al8 ) reported that VMO/VL ratios ranged from 0.99 to 1.0 during leg raise exercises in a supine position. In the present study, a VMO/VL ratio of 0.92 was obtained in the hard plate group.…”
Section: Discussionmentioning
confidence: 99%